PELATIHAN PRESENTASI DENGAN MEDIA APLIKASI MICROSOFT OFFICE POWERPOINT PADA SISWA KELAS 6 Di SD BARUNA BATUBULAN - I Gede Adnyana; I Gusti Made Ngurah Desnanjaya; Kadek Suryati; Ni Putu Suci Meinarni; Bagus Kusuma Wijaya; Made Vera Sugiyama Ria; Putu Candra Kharisma Dewi; Ida Ayu Wiwit Lastari; David Maulana Suripati; I Gusti Ngurah Bagus Widiatmika; Masridho Suriyono (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
The purpose of this service is to help convey information related to the introduction of the basics of presentations and their media to provide them with basic public speaking experience by making and carrying out simple interactive presentations that will be developed and used at the next level and even up to the world of work. One of the uses of technology in this digital era is the use of digital applications to assist presentation activities. One of the applications commonly used in today's circles is the Microsoft Office PowerPoint application. This application can be accessed via computers based on the Windows operating system and Apple Mac OS. In this service, we will introduce this application as an illustration of using the application to help with presentation activities. However, the level of confidence of elementary school students in speaking in public is low. Even though this skill is a mandatory stage that must be passed and will be useful for the future. From these problems, community service activities are carried out by providing basic knowledge of introduction to presentations and the basics of public speaking skills to increase students' confidence to speak in public. The implementation method used in this activity is (1) providing basic material in good and correct presentations, (2) introducing commonly used media, (3) providing opportunities and assistance in simple presentation practices. The result of this activity is an increase in students' basic knowledge and skills in presentations, so that students become more confident to be able to appear in public along with the possibility to improve their abilities to be better than before.